1997
DOI: 10.1016/s0042-6989(97)00156-9
|View full text |Cite
|
Sign up to set email alerts
|

Object detection in natural backgrounds predicted by discrimination performance and models

Abstract: Many models of visual performance predict image discriminability, the visibility of the difference between a pair of images. We compared the ability of three image discrimination models to predict the detectability of objects embedded in natural backgrounds. The three models were: a multiple channel Cortex transform model with within-channel masking; a single channel contrast sensitivity filter model; and a digital image difference metric. Each model used a Minkowski distance metric (generalized vector magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 6 publications
0
62
0
1
Order By: Relevance
“…Filter-based models have been enormously successful in describing early visual processing, and it is not my goal at this time to apply each of these models to a change detection task or to advocate one of these models over another (Bell & Sejnowski, 1997;Graham, 1992;Lades et al, 1993;Malik & Perona, 1990;Rohaly, Ahumada, & Watson, 1997;see Landy & Movshon, 1991, for a review). 7 Rather, my goal is to distill from these models a simplified and easily implemented approach tailored to the demands of a change detection task.…”
Section: The Bolar Representationmentioning
confidence: 99%
“…Filter-based models have been enormously successful in describing early visual processing, and it is not my goal at this time to apply each of these models to a change detection task or to advocate one of these models over another (Bell & Sejnowski, 1997;Graham, 1992;Lades et al, 1993;Malik & Perona, 1990;Rohaly, Ahumada, & Watson, 1997;see Landy & Movshon, 1991, for a review). 7 Rather, my goal is to distill from these models a simplified and easily implemented approach tailored to the demands of a change detection task.…”
Section: The Bolar Representationmentioning
confidence: 99%
“…Although there have been a number of studies of detection in natural backgrounds (16)(17)(18)(19)(20)(21)(22)(23), they have not directly addressed these questions, and have either tested only a small number of natural stimuli (16,17,19,20), tested natural stimuli with altered statistical properties (21,22), or used experimental paradigms not representative of natural detection tasks (16,(18)(19)(20)23). These latter studies are not as representative of natural tasks, because observers were allowed to directly compare the same image with and without the added target, an advantage that is not normally available under real-world conditions.…”
mentioning
confidence: 99%
“…It is therefore of great practical value to have computational visual differences or distinctness measures which can be applied to evaluate image displays, (virtual) scene generators, image compression methods, image reproduction methods, camouflage measures, and traffic safety devices [9], [25]. Rohaly et al [26] recently showed that image discrimination models that quantify the visibility of the differences between a pair of images can predict the visual distinctness of objects in natural backgrounds. Often implicit in the interpretation of visual search tasks is the assumption that the detection of targets is determined by the feature-coding properties of low-level visual processing [9].…”
Section: Application: a Computational Model To Predict The Visual Tarmentioning
confidence: 99%